Warfarin-induced spontaneous retroperitoneal hemorrhage from the renal vein: A rare case with an uncommon etiology - Nasr, Mohamed A. (Qatar Med J, 2019)
The overall rate of major bleeding in patients with atrial fibrillation receiving warfarin therapy is approximately 4%. Among these 4% patients, spontaneous retroperitoneal hemorrhage (SRH) is a rare but potentially lethal complication with a nonspecific presentation that can lead to missed or delayed diagnosis. The current literature provides little direction for diagnosis and management of such cases. Anticoagulation-related SRH is associated with a high mortality rate (approximately 20%). Despite the vague presentation, prompt diagnosis is crucial to reverse the anticoagulation and prevent further bleeding. Contrast-enhanced computed tomography (CT) of the abdomen is the imaging modality of choice in suspected cases. Patients with SRH require aggressive treatment with blood transfusions, interventional radiological procedures, percutaneous drainage or surgical evacuation of the hematoma. We report a case of warfarin-induced SRH from the renal vein in a patient who presented to our emergency department with acute, nonspecific abdominal pain and shock. We diagnosed the patient with warfarin-induced SRH on the basis of clinical suspicion and characteristic CT findings. We initially treated the patient conservatively, followed by embolization of the right renal artery during the late course of hospital stay, and he was discharged with good recovery. SRH should be considered in the differential diagnosis of abdominal pain, hypotension, and/or decreased hemoglobin levels in patients receiving anticoagulation therapy, especially in those with preexisting end-stage renal disease.